Effects of once‐weekly semaglutide on appetite, energy intake, control of eating, food preference and body weight in subjects with obesity. Issue 9 (5th May 2017) - Blundell, John; Finlayson, Graham; Axelsen, Mads; Flint, Anne; Gibbons, Catherine; Kvist, Trine; Hjerpsted, Julie B.
Abstract : Aim: The aim of this trial was to investigate the mechanism of action for body weight loss with semaglutide. Materials and methods: This randomised, double‐blind, placebo‐controlled, two‐period crossover trial investigated the effects of 12 weeks of treatment with once‐weekly subcutaneous semaglutide, dose‐escalated to 1.0 mg, in 30 subjects with obesity. Ad libitum energy intake, ratings of appetite, thirst, nausea and well‐being, control of eating, food preference, resting metabolic rate, body weight and body composition were assessed. Results: After a standardised breakfast, semaglutide, compared with placebo, led to a lower ad libitum energy intake during lunch (−1255 kJ; P < .0001) and during the subsequent evening meal ( P = .0401) and snacks ( P = .0034), resulting in a 24% reduction in total energy intake across all ad libitum meals throughout the day (−3036 kJ; P < .0001). Fasting overall appetite suppression scores were improved with semaglutide vs placebo, while nausea ratings were similar. Semaglutide was associated with less hunger and food cravings, better control of eating and a lower preference for high‐fat foods. Resting metabolic rate, adjusted for lean body mass, did not differ between treatments. Semaglutide led to a reduction from baseline in mean body weight of 5.0 kg, predominantly from body fat mass. Conclusion: After 12 weeks of treatment, ad libitum energy intake was substantially lower with semaglutide vs placebo with a corresponding loss of body weight observed with semaglutide. In addition to reduced energy intake, likely mechanisms for semaglutide‐induced weight loss included less appetite and food cravings, better control of eating and lower relative preference for fatty, energy‐dense foods. Video Abstract: A free Video Abstract to accompany this article is available at: https://player.vimeo.com/video/218478638 .